Job Stress and Job Satisfaction Among Nurses in Mardi Waluyo Hospital Blitar - Ahsan, Ahsan; Cahyaning Pradyanti, Adine Yenie (Universitas Airlangga, 2015)
Introduction: Nurses as a professional worker in hospitals are often getting job stress that cause disturbance physiology, psychology, and behavior. A study had shown that job stress in a high level would decrease the job satisfaction. The objectived of this research was to analyze the relation of job stress with the nurse job satisfaction in Mardi Waluyo Hospital in Blitar City. Methods: This research used cross-sectional as the method to conduct this research by examining the relation among variables using Rank-Spearman. Sample of this research was the total sampling, whichÂ the total of all nurses that work in the Hospital, Mardi Waluyo in Blitar City. All of the respondents filled out the questionnaires about stress that occur while working and the job satisfaction. Total of respondents were 61 nurses.Results:Â The result of Rank-Spearman showed the value of -0,674; there was an inverted relation among variables with a strong relationship level, The significance in this research was 0,000 with a confidence interval of 95% (p-value). Discussion:Â there was the more stress those nurses got, then there would be less job satisfaction.Key words :Job Stress, Job Satisfaction, Nurse